The immunomodulatory activity of dioscorea alata on spleen histology of rats induced with 50% alcohol - Makiyah, Sri Nabawiyati Nurul; Zahra, Adelia Nabilah (Science Midwifery, 2025)
Dioscorea alata is frequently consumed and has several health advantages. The immune system-protecting spleen may be protected by bioactive substances in Dioscorea alata tubers. This study examined the influence of immunomodulatory ethanol extract of Dioscorea alata (EEDA) on the diameter of the white pulp of the spleen in 50% alcohol-induced rats (Rattus norvegicus). This research is quasi-experimental using post-test only controlled group design. Twenty-five Rattus norvegicus were separated into five groups. The normal control group (C) received Carboxymextyl Cellulose (CMC), the negative control group (NC) received CMC and 50% alcohol, and three groups received EEDA at doses of 50, 250, and 500 mg/kg for 14 days and 50% alcohol. The diameter of the white pulp of the spleen data analyzed with Kruskal-Wallis and Mann-Whitney tests. The study found a significantly increase in the diameter of the white pulp of the spleen (p<0.05) in the negative control group, EEDA doses of 50 and 250 mg/kg. The control group and EEDA doses 500 mg/kg groups had smaller the diameter of the white pulp of the spleen. The conclusions of this research proved that EEDA has an immunomodulatory activity, EEDA was immunostimulant at doses 50 and 250 mg/kg and immunosuppressant at doses 500 mg/kg.